META-ANALYSIS: THE DETERMINATION OF FACTORS THAT INFLUENCE MUSTAHIK REVENUE - Abdul Alaa Asy Syafiq; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the factors that influence mustahiq income in Indonesia using the meta-analysis method after through sample selection. It was found that the variables used were zakat funds, assistance, length of business and education level. This study took a population of journals and manuscripts published on google scholar. This research accumulates and integrates existing studies using the meta-analysis technique developed by Hunter et al. (1982) on 15 publication samples. The results of this study indicate that the overall independent variables namely, zakat funds, assistance, education level and length of business, have a significant effect on the dependent variable of mustahiq income. The results of independent variable calculations state that there is a consistency of calculated results that are significant from the independent variable on the dependent variable, the dependent variable which is mustahiq income, is consistently influenced by its independent variables.Keywords: mustahiq income, productive zakat, assistance, education level, length of business, Meta-analysisREFFERENCE Badan Pusat Statistik. (n.d.). Distribusi persentase penduduk dan kepadatan penduduk menurut provinsi 2000-2013. Jakarta: BPS.Badan Pusat Statistik. Jumlah dan persentase penduduk miskin, garis kemiskinan, indeks kedalaman kemiskinan (P1), dan indeks keparahan kemiskinan (P2) menurut provinsi, 2007-2009 (maret), 2010-2011, 2012 (maret). Jakarta: BPS.Fitri, Maltuf. (2017). Pengelolaan zakat produktif sebagai instrumen peningkatan kesejahteraan umat. Economica: Jurnal Ekonomi Islam, 8(1), 149-173. DOI: http://dx.doi.org/10.21580/economica.2017.8.1.1830Garry. (2011). Pengaruh dana zakat produktif terhadap keuntungan usaha mustahik penerima zakat. Skripsi tidak diterbitkan. Semarang: Fakultas Ekonomi dan Bisnis Universitas Diponegoro.Glass, G. V. (1976). Primary, secondary, and meta analysis of research. Educational Researcher, 5(10):3-8. DOI: 10.2307/1174772Hariandja, Marihot T.E. (2002). Manajemen sumber daya manusia. Jakarta: Grasindo.Hasbullah. (2003). Dasar-dasar llmu pendidikan. Jakarta: Rajagrafindo Persada.Hawkins, I Best, R. J. Coney, K. (1998). Consumer behavior: Building market strategy. USA: Irwin/Mc Graw-Hill.Hunter, F. S. (1990). Methods of meta analysis: Correcting error and bias in research findings. California: Sage Publications. Hunter, J. (1982). Meta-analysis: cumulating research findings accros studies. Beverly Hills: CA. Sage Publications.Ihsan, Fuad. (2006). Dasar-dasar kependidikan, Jakarta: Rineka Cipta.Instruksi presiden no.15 tahun 1974Jurnal ekonomi islam P3EI UII, 2007Mangkunegara, A. A. A. P. (2015) Manajemen sumber daya manusia perusahaan. Jakarta: PT. Remaja Rosdakarya.Notoatmojo, S. (2010). Pengembangan sumber daya manusia. Penerbit : Rineka Cipta.Qardhawi, Y. (2002). Fiqh al-zakah.Beirut: Muassasat al-Risalah.Rohman, Dani. (2018). Pengaruh jumlah ZIS yang diterima, jumlah anggota keluarga, dan lama usaha mustahik penerima ZIS produktif terhadap kesejahteraan ekonomi (studi pada LAZISMU Sragen). Skripsi tidak diterbitkan. Surakarta: IAIN Surakarta.Toriquddin, M. (2015). Zakat Kota Malang perspektif maqashid al syariah ibnu ‘Asyur. Jurnal Ulul Albab, 16(1), 62-79.Zuhayli, W. (1997). Al-fiqh al-islami wa adillatuhu.Damascus: Dar Al-Fikr.